Barriers and facilitators of care for diverse patients: Nurse leader perspectives and nurse manager implications. (27th October 2017) - Ogbolu, Yolanda; Scrandis, Debra A.; Fitzpatrick, Grace
Abstract : Objective: To examine chief nurse executives' perspectives on: (1) the provision of culturally and linguistically appropriate services in hospitals and (2) to identify barriers and facilitators associated with the implementation of culturally and linguistically appropriate services. Background: Hospitals continue to face challenges providing care to diverse patients. The uptake of standards related to culturally and linguistically appropriate services into clinical practice is sluggish, despite potential benefits, including reducing health disparities, patient errors, readmissions and improving patient experiences. Method: A qualitative study with chief nurse executives from one eastern United States (US). Data were analysed using content analysis. Results: Seven themes emerged: (1) lack of awareness of resources for health care organisations; (2) constrained cultural competency training; (3) suboptimal resources (cost and time); (4) mutual understanding; (5) limited workplace diversity; (6) community outreach programmes; and (7) the management of unvoiced patient expectations. Conclusions: As the American population diversifies, providing culturally and linguistically appropriate services remains a priority for nurse leaders. Being aware and utilizing the resources, policies and best practices available for the implementation of culturally and linguistically appropriate services can assist nursing managers in reaching their goals of providing high quality care to diverse populations. Implications for Nursing Management: Nurse managers are key in aligning the unit's resources with organisational goals related to the provision of culturally and linguistically appropriate services by providing the operational leadership to eliminate barriers and to enhance the uptake of best practices related to culturally and linguistically appropriate services.